2020
DOI: 10.2147/idr.s258744
|View full text |Cite
|
Sign up to set email alerts
|

<p>Echinocandins versus Amphotericin B Against <em>Candida tropicalis</em> Fungemia in Adult Hematological Patients with Neutropenia: A Multicenter Retrospective Cohort Study</p>

Abstract: Background: Candida tropicalis is the most common non-albicans Candida species identified in immunocompromised patients, which often appears with high mortality. However, data on the outcomes of treatment for Candida tropicalis fungemia in patients with neutropenia remain limited. Methods: In the present study, 90 neutropenic adult patients with proven Candida tropicalis fungemia, who received initial antifungal therapy, were retrospectively analyzed. Results: These results revealed that the overall 8-day and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“… 1 , 21 Five studies reported on the 30-day mortality rates in C. tropicalis candidaemia patients ranging from 32% to 52%. 2 , 10 , 11 , 22 , 23 Overall mortality rates in paediatric patients with invasive C. tropicalis infections were 26%–40%. 24 , 25 …”
Section: Resultsmentioning
confidence: 99%
“… 1 , 21 Five studies reported on the 30-day mortality rates in C. tropicalis candidaemia patients ranging from 32% to 52%. 2 , 10 , 11 , 22 , 23 Overall mortality rates in paediatric patients with invasive C. tropicalis infections were 26%–40%. 24 , 25 …”
Section: Resultsmentioning
confidence: 99%
“…The past 15 years have seen an acceleration in antifungal drug development, culminating in an armamentarium of systemic antifungal agents including 5 classes of drugs including amphotericin B (AmB), the azoles, and the echinocandins [41] . Although their in vitro inhibitory and direct fungicidal effects are well characterised, antifungals also have indirect, immune system-mediated effects on fungi, which are only now coming to light [42] .…”
Section: Host-modulating Antimicrobialsmentioning
confidence: 99%
“…The past 15 years have seen an acceleration in antifungal drug development, culminating in an armamentarium of systemic antifungal agents including 5 classes of drugs including amphotericin B (AmB), the azoles, and the echinocandins 35 . Although their in vitro inhibitory and direct fungicidal effects are well characterised, antifungals also have indirect, immune system-mediated effects on fungi, which are only now coming to light 36 .…”
Section: Host-modulating Antimicrobialsmentioning
confidence: 99%